Key Factors Affecting Customer Citizenship Behavior in Small and Medium-sized Enterprises - Shiratina, Aldina; Utama, Andyan Pradipta; Ali, Anees Janee (Jurnal Manajemen Bisnis, 2025)
Research aims: This research aims to analyze how customer satisfaction and costumer citizenship behavior (CCB) are impacted by price justice and product quality. Design/Methodology/Approach: A quantitative methodology was employed utilizing survey data from patrons at several rest stops along the Cipali Toll Road. To examine the relationship between variables, structural equation modeling was utilized. The research population consists of customers who utilized the Cipali Toll rest area facilities at least occasionally over the past year. The research sample was selected using a judgmental sampling method as an element of non-probability sampling according to the target population. Research findings: The study findings indicate that CCB and customer satisfaction are positively and significantly impacted by price justice and product quality. While strong product quality boosts customer satisfaction and stimulates positive customer behavior, price justice has a substantial impact on both customer satisfaction and voluntary product promotion. Furthermore, costumer satisfaction mediates the relationship between price justice and CCB, as well as between product quality and CCB.Theoretical Contribution/Originality: This study emphasizes how crucial customer satisfaction is in enhancing the positive impact of fair prices and high-quality products on customers' voluntary behavior. It offers empirical support for the argument that fair prices and high-quality products are important in promoting positive behavior and customer loyalty.Practitioners/Policy Implications: To gain the trust and loyalty of customers, businesses must maintain excellent product quality, comprehend and apply fair pricing strategies, and guarantee price justice. Emphasizing excellent customer service and delivering high-quality items should be the primary focus in boosting client loyalty and positive behavior. Research Limitations/Implications: To determine whether the study results are applicable to other sectors and locations, more research is recommended in the rest areas along the Cipali Toll Road. Longitudinal studies are suggested to monitor changes in customer satisfaction and CCB over time to furrther understand the connection and spot patterns and shifts in customer perceptions.